Critical Issues in Ionospheric Data Quality and Implications for Scientific Studies. Issue 5 (21st May 2019) - Araujo‐Pradere, E.; Weatherhead, E. C.; Dandenault, P. B.; Bilitza, D.; Wilkinson, P.; Coker, C.; Akmaev, R.; Beig, G.; Burešová, D.; Paxton, L. J.; Hernández‐Pajares, M.; Liu, J.‐Y.; et al.
Abstract: Ionospheric data are valuable records of the behavior of the ionosphere, solar activity, and the entire Sun‐Earth system. The data are critical for both societally important services and scientific investigations of upper atmospheric variability. This work investigates some of the difficulties and pitfalls in maintaining long‐term records of geophysical measurements. This investigation focuses on the ionospheric parameters contained in the historical data sets within the National Oceanic and Atmospheric Administration National Geophysical Data Center and Space Physics Interactive Data Resource databases. These archives include data from approximately 100 ionosonde stations worldwide, beginning in the early 1940s. Our study focuses on the quality and consistency of ionosonde data accessible via the primary Space Physics Interactive Data Resource node located within the National Oceanic and Atmospheric Administration National Geophysical Data Center and the World Data Center for Solar‐Terrestrial Physics located in Boulder, Colorado. We find that, although the Space Physics Interactive Data Resource archives contained an impressive amount of high‐quality data, specific problems existed involving missing and noncontiguous data sets, long‐term variations or changes in methodologies and analysis procedures used, and incomplete documentation. The important lessons learned from this investigation are that the data incorporated into an archive must have clear traceability back to the primary source, including scientific validation by the contributors, and that the historical records must have associated metadata that describe relevant nuances in the observations. Although this report only focuses on historical ionosonde data in National Oceanic and Atmospheric Administration databases, we feel that these findings have general applicability to environmental scientists interested in using long‐term geophysical data sets for climate and global change research. Key Points: This work describes problems found within long‐term ionospheric records, likely caused by distributed storage system The problems found still persist, and there is no appearance of reparation Ionospheric data are valuable records of the behavior of the ionosphere, solar activity, and the entire Sun‐Earth system